Profile of the Lower Respiratory Tract Microbiome in Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome and Lung Disease - Chen, Zhen; Tian, Ya; Wang, Yu; Zhao, Hongxin; Chen, Chen; Zhang, Fujie (Frontiers in Microbiology, 2022)
After the HIV-infected person enters the onset period, due to the significant reduction or deficiency of the body’s immune function, a variety of opportunistic infections may occur, affecting various systems and organs throughout the body(Tan et al., 2012). The objectives were to explore the relationship between immune status and microbial communities in the lungs. A total of 88 patients (80 [91%] HIV-infected and 8 [9%] non-HIV-infected) were enrolled in our cohort, and a total of 88 samples of bronchoalveolar lavage fluid(BALF) were obtained by bronchoscopy from Jan, 2018, and Jul, 2018.In this Cross-sectional study, we describe differences in the pulmonary microbiome of patients with HIV in different immune status. The diversity of bacteria in the lungs of HIV-infected persons is lower than that of non-HIV-infected persons(p < 0.05). There was a difference in the composition and distribution of microbiota and fungi between the HIV and non-HIV groups (p < 0.01). The fungus in the BALF of HIV-infected patients increased compared with that of non-infected patients. We observed that with the decrease of CD4, the diversity bacteria and fungi in the BALF of HIV-infected patients increased. Linear regression analysis showed that Pneumocystis, Cryptosphaeria, Candida, Aspergillus were negatively correlated with CD4(Wilcoxon, p < 0.05). The samples collected from the HIV- infected patients displayed a significantly different pattern relative to those from the non-HIV group. Changes in the host's immune status will cause changes in the diversity and structure of the lower respiratory tract microorganisms.